Автобиография и правда: Аввакум Петрович о Настасье Марковне - Yury Zaretskiy (Avtobiografija, 2013)
The article discusses the portrayal of the author’s wife in Zhitie (Life Story), the most well-‐known pre-‐modern Russian autobiography written by the archpriest Avvakum (1621/2 – 1682). The main question addressed in the article is the credibility of this portrayal. Its main conclusion suggests that while searching for historical truth in autobiographical stories we should take into consideration that they were written not for us but for some other readers, and that this difference of addressees complicates our search